MENTAL HEALTH PADA PANDEMIC COVID 19 BAGI GURU DI SMAN 1 KREMBUNG SIDOARJO - Yandika Fefrian Rosmi; Achmad Nuryadi; Mulyono; I Gede Darma Utamayasa; Bayu Akbar Harmono; Riga Mardhika (Universitas PGRI Adi Buana Surabaya, 2022)
Community service through this training activity aims to provide teachers with an understanding of the importance of mental health at SMAN 1 Krembung. This activity was attended by 65 participants from a combination of employees and teachers of SMAN 1 Krembung. The method of implementing the activity includes 4 stages 1). Observation, 2). Implementation of Activities, 3). Activity Achievement, and 4). Evaluation. The training/workshop implementation activities have been carried out well, as can be seen from the enthusiasm of the training participants both during the delivery of training materials and during discussions. The success of the training was also aimed at increasing the average pretest and posttest scores, with a score of 65.5 for the pretest score and 75.5 for the posttest assessor.